EFEKTIFITAS PELAYANAN SOSIAL ANAK DI BIDANG PENDIDIKAN OLEH PANTI ASUHAN YAYASAN AMAL-SOSIAL AL-WASHLIYAH KELURAHAN GEDUNG JOHOR KECAMATAN MEDAN JOHOR - Dodi Setiadi Lase (Welfare StatE, 2012)
Neglected children is one of social welfare problems that exist in all societies. There are many social problems that cause child neglect, such as socio-economic issues, social psychology, and parents who are not responsible for their obligation to meet the needs of their children. It is inevitable that the majority of child neglect directly related to poor socioeconomic conditions of families, so parents are not able to meet the needs of children. Neglection  is causing the childern do not have enough opportunities to grow and develop naturally either physically, spiritually, and socially. Handling of childern welfare has been done both by the government and private sector through the social system and non-nursing home. One of the ways in which to overcome this problem is through the orphanage who are willing to accommodate the displaced children, which were given the same facilities as other children receive. The research was conducted at the Orphanage Foundation for Socio-Al-Amal Village Washliyah Medan District of Johor Johor House. This research used descriptive method with qualitative approach. To obtain the necessary data, this study used data collection techniques literature study and field study consisting of observation, interview, questionnaire filling. The results can be seen that foster children residing in Al-Washliyah Orphanage is treated with adequate care. This is evident from the relationship between the caregiver Panti well with foster children who will receive them and make them like his own family and children development in terms of physical, spiritual and social are well developed. Keywords: Social Services, Child Care, Orphanage